Psychological and Pedagogical Features of Teaching Students with Visual Deprivation in Training to Work on a Personal Computer - Sokolov V. V. (Moscow State University of Psychology and Education, 2015)
This article discusses how children with profound sight impairment percieve visual information from a computer screen using synthesized speech and the tactile display system Braille. Describes research of characteristics of user skills development in children with visual deprivation. Illustrated are the main differences in the perception of information from the screen of the user's computer using a visual interface, and users forced to use special software to non-visual access. Provide the most significant results of research and a number of methodical recommendations on educating children of this category in work on the personal computer without visual control. The article may be interest to teachers of informatics, teaching students with profound visual impairment, for parents with children in this category, as well as for scientists, whose professional interests are in the area of pedagogy of the blind